Salivary MMP‐13 gender differences in periodontitis: A cross‐sectional study from Sweden. Issue 5 (15th September 2017) - Virtanen, Eunice; Yakob, Maha; Tervahartiala, Taina; Söder, Per‐Östen; Andersson, Leif C.; Sorsa, Timo; Meurman, Jukka H.; Söder, Birgitta
Abstract: We investigated serum and saliva concentrations of matrix metalloproteinases, MMP‐8, MMP‐9, and MMP‐13, and their tissue inhibitor TIMP‐1, in a group of patients with and without periodontitis from Sweden. The hypothesis was that these biomarkers are higher in the periodontitis patients. Ninety patients participated in this cross‐sectional study. Fifty‐one patients had periodontitis whereas 39 were periodontally healthy. Saliva and serum samples were analyzed with immunofluorometric, enzyme‐linked immunosorbent assay and western blot. Results were statistically analyzed with independent t test, Mann–Whitney U test, Bonferroni corrections, and regression analyses. MMP‐13 was not detected in serum, but in saliva, higher values were found among the periodontally healthy compared with periodontitis subjects (0.32 ± 0.26 vs. 0.21 ± 0.23 ng/ml, p < .05). Female gender and clinical attachment loss were the explanatory factors for higher salivary MMP‐13 values with odds ratio 3.08 (95% confidence interval [1.17, 8.11]) and 3.57 (95% confidence interval [1.08, 11.82]), respectively. No statistically significant differences between groups were found in serum and saliva values of MMP‐8, MMP‐9, and TIMP‐1. Contrary to our hypothesis, no statistically significant differences between patients with and without periodontitis were seen in MMP‐8, MMP‐9, and TIMP‐1 values. However, higher MMP‐13 concentrations in saliva were associated with female gender and higher clinical attachment loss. Metabolism of MMP‐13 may thus have some gender implications in periodontitis.